2020
DOI: 10.21203/rs.3.rs-40461/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Emerging Role of Neutrophil Extracellular Traps in Severe Acute Respiratory Syndrome Coronavirus 2 (COVID-19)

Abstract: Abstract The novel coronavirus SARS-CoV2 causes COVID-19, a highly pathogenic viral infection threatening millions. The majority of those infected are asymptomatic or mildly symptomatic showing typical clinical signs of common cold. However approximately 20% of the patients can progress to acute respiratory distress syndrome (ARDS) and eventually death in about 5% of cases. Recently, angiotensin-converting enzyme 2 (ACE2) has been shown to be a functional receptor for v… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 19 publications
1
41
1
Order By: Relevance
“…NETosis is implicated in severe COVID-19 pathology through transcriptomics, proteomics, and circulating cell-free DNA Several studies have reported associations between SARS-CoV-2 infection and NETs [47][48][49] . NETs are extracellular webs of chromatin that contain highly reactive oxidative enzymes such as myeloperoxidase which have the ability to capture and neutralize microbes including viruses 21 , but in excess can cause tissue damage and microvascular thrombosis 50 .…”
Section: Longitudinal Analyses Reveal Diverging Pathway Dynamics Between Survivors and Non-survivors Among Severe Patientsmentioning
confidence: 99%
“…NETosis is implicated in severe COVID-19 pathology through transcriptomics, proteomics, and circulating cell-free DNA Several studies have reported associations between SARS-CoV-2 infection and NETs [47][48][49] . NETs are extracellular webs of chromatin that contain highly reactive oxidative enzymes such as myeloperoxidase which have the ability to capture and neutralize microbes including viruses 21 , but in excess can cause tissue damage and microvascular thrombosis 50 .…”
Section: Longitudinal Analyses Reveal Diverging Pathway Dynamics Between Survivors and Non-survivors Among Severe Patientsmentioning
confidence: 99%
“…In general, the predisposing factors for development of the cytokine storm consist of a diverse combination of mechanisms, involving viral escape associated with genetic defects of host defense, as well as other immunological abnormalities, such as high rate of neutrophil in ltration into target tissues. The infection and consequent activation of neutrophilic network and thrombocytogenesis lead to multiple organ failure (6,8). This mechanism of immunopathogenesis has been proposed as a determinant in the worsening of infection, contributing to the high morbidity and lethality seen in COVID-19 (1).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil responsive chemokine signature, secretion of NET (Neutrophil extra-cellular traps), and increased infiltration of neutrophils were found to be associated with severe cases of COVID-19 (29)(30)(31)(32).…”
Section: Immune Cells Immune Cell Function In Inflammation and Homeostasis Emerging Clinical Relevance In Sars-cov-2 Infection Neutrophilmentioning
confidence: 97%